Uncontrolled hypertension among adult hypertensive patients in Addis Ababa public hospitals: A cross-sectional study of prevalence and associated factors. - Asmamaw Deguale Worku; Asinake Wudu Gessese (PLoS ONE)
Background In 2019, 77% of women and 82% of men with hypertension had uncontrolled hypertension worldwide. Uncontrolled hypertension can cause stroke, myocardial infarction, heart failure, renal failure, dementia, blindness, and death. However, most of the studies used the previous seventh joint national committee classification to classify hypertensive patients as either controlled or uncontrolled. This study aimed to assess the prevalence and associated factors of uncontrolled hypertension among adult hypertensive patients at public hospitals in Addis Ababa, Ethiopia. Methods From April 12 to May 12, 2024, three public hospitals in Addis Ababa employed a hospital-based cross-sectional study design with 408 hypertensive patients. Systematic random sampling was used to select the study participants. We used a structured interview questionnaire and chart review and took physical measurements. Data were entered into Epidata and analyzed using the statistical package for social science version 25. A logistic regression model was used to identify factors associated with uncontrolled hypertension at a P-value < 0.05 with a 95% confidence interval. Results The prevalence of uncontrolled hypertension among hypertensive patients at public hospitals in Addis Ababa was 66.2% (95% CI: 61.6%, 70.8%). After adjusted analysis, age ≥ 60 years (AOR = 2.88, 95% CI: 1.37, 6.04), the presence of comorbidities (AOR = 2.21, 95% CI: 1.23, 3.96), being overweight (AOR = 2.25, 95% CI: 1.20, 4.24), non-adherence to antihypertensive medication (AOR = 5.21, 95% CI: 2.76, 9.83), non-adherence to a low-salt diet and dietary approaches to stop hypertension (AOR = 2.74, 95% CI: 1.35, 5.53), taking three or more antihypertensive medications (AOR = 3.10, 95% CI: 1.16, 8.25), and non-adherence to physical exercise (AOR = 2.84, 95% CI 1.49, 5.39) were factors associated with uncontrolled hypertension. Conclusions Uncontrolled hypertension was very high in public hospitals in Addis Ababa, Ethiopia. Key factors for uncontrolled hypertension are non-adherence to antihypertensive medications, use of multiple medications, lack of physical exercise, and low adherence to low salt and dietary approaches to stop hypertension. To address these, enhancing patient education on medication adherence, promoting lifestyle changes, and leveraging digital health tools, like mobile apps, for real-time support and adherence tracking are recommended.